ANALISIS KINERJA PORTOFOLIO OPTIMAL PADA SAHAM INDEKS BISNIS27, JII, LQ45 DAN KOMPAS100 MENGGUNAKAN SINGLE INDEX MODEL PERIODE 2010-2012 - Supriyanto .; Ahmad Yani (Journal Of Communication Education, 2014)
ABSTRACT Investments are placement of funds in certain assets in the hope of future profits. Investing in stocks is an investment option that the public interest at this time, given the greater benefits, despite having a greater risk. So investors should be diversify stock in order to provide optimal benefits and minimize risks. This study discusses the implementation of Single Index Model to establish the optimal portfolio, which aims to optimize returns and minimize risk. Applied research on stock index Bisnis27, JII, LQ45 and Kompas100. Formation and observation in January 2010 to December 2012. Portfolio performance is measured using the Sharpe index, Treynor and Jensen. These results indicate that the optimal portfolio provides higher returns than the market index, so it can be considered investors in investing. The average return per quarter are Bisnis27 by 6.56%, 7.43% of JII, LQ45 by 7.58% and 10,22% for Kompas100. Performance analysis using Shape and Treynor index shows that the optimal portfolio that has the best performance in a row that Kompas100, LQ45, JII and Bisnis27, while Jensen index shows that the optimal portfolio is better than the performance of the market index. However, based on statistical analysis concluded there is no significant difference in the performance of the optimal portfolio fourth.                                                 Keyword: Single Index Model, Optimal portfolio, Sharpe Index, Treynor Index, Jensen Index.